Parents' perspectives and experiences of having a child with hereditary hearing loss - Ross, Sinead Amber (Division of Human Genetics, 2017)
Congenital hearing loss (HL) occurs in 1-2 per 1000 newborns globally. Of all the congenital diseases that occur worldwide, HL remains the most disabling, with the highest rate for age-standardised disability life years and is a significant public health concern particularly in the developing world. In South Africa, 6 in 1000 newborns, have disabling HL. Genetic aetiology accounts for half of the cases of prelingual HL and of these 70% are nonsyndromic. There is ongoing research into the genetic basis of HL in the South African setting as at present, genetic testing for HL is largely uninformative in most African populations. Previous studies have examined the psychosocial challenges experienced by parents related to their child's HL, but in South Africa there have been no studies investigating the hereditary aspects of HL and how they may be related to the experiences of parents. Furthermore, the understanding and comprehension of genetics concepts is unknown in this population and needs to be explored before appropriate genetic counselling may be provided to parents of children with hereditary HL. Therefore, the aim of this research was to examine the perspectives, experiences and understanding of parents, whose children are deaf, potentially due to a nonsyndromic genetic aetiology, in a selected setting in Cape Town. Eleven participants were recruited through the clinical genetics service at Red Cross War Memorial Children's Hospital and the Dominican School for Deaf Children in Cape Town. Semi-structured interviews were conducted, and the transcripts analysed using the framework approach for data analysis. Through this approach, five themes were identified relating to the experience of parenting a deaf child, parents' understanding of the cause of their child's HL and the way that their child's difference or normalcy is perceived. Most parents were unable to identify the cause of their child's HL unless there were previous cases of HL in the family, but almost all were interested in pursuing genetic testing to assist them in finding answers. The time from the diagnosis had been an emotional and confusing time for many of the participants, who found means to cope and adapt to their child's HL through faith and support systems. Each of the participants had a unique experience with regards to their child's HL, some needing to make sacrifices and overcome practical challenges in order to provide for their child. Participants both rejected shame and pity with regards to their child's HL and embraced that their child was different, part of the Deaf world, but that this difference does not define them. This research could influence the genetics services provided for this population. It is imperative to understand the experiences and comprehension of this population so that improvements can be made to provide appropriate services.